Landscape features associated to the occurrence of Amblyomma sculptum ticks: an application of zero inflated regression models - Pedro, Thiago Bernardo; Silveira, Andrea Kill; Tassinari, Wagner de Souza (Brazilian Journal of Veterinary Medicine, 2016)
ABSTRACT. Bernardo-Pedro T., Silveira A.K. & Tassinari W.S. Landscape features associated to the occurrence of Amblyomma sculptum ticks: an application of zero inflated regression models. [Características de paisagem associadas à ocorrência de carrapatos Amblyomma sculptum: uma aplicação dos modelos de regressão inflacionados de zeros.] Revista Brasileira de Medicina Veterinária, 38(supl. 3):39-46, 2016. Programa de Pós-Graduação em Ciências Veterinárias, Departamento de Parasitologia Animal, Universidade Federal Rural do Rio de Janeiro, BR-465, km 7, Seropédica, RJ 23890-000, Brasil. E-mail: thiago.b.pedro@gmail.com The aim of the present study was to analyze the association between landscape features and occurrence of A. sculptum ticks, using zero inflated regression models. A total of 503 ticks were collected during the period of the research. Most of them were captured in sites related to the following features: 20-40m altitude (93.64%), 0-2.5% declivity (57.65%), plain land (93.04%), albaqualf type of soil (52.68%), presence of capybaras (56.06%) and high occurrence favorability of A. sculptum (84.89%). Regarding the non-inflated part of the bivariate models, all variables were significant, which means all of them contribute to A. sculptum occurrence. In the final multivariate model, only geomorphology and type of soil were relevant variables to explain A. sculptum occurrence. In conclusion, landscape features – especially geomorphology and type of soil – are associated to A. sculptum abundance in the research area, what indicates that these variables should be taken into consideration when planning tick control programs.